Comparative analysis of intelligent reflecting surfaces and AF/DF relaying for energy efficient wireless communication - Kuldeep Yadav; Himanshu Parashar; Soumen Mondal (EURASIP Journal on Wireless Communications and Networking)
Abstract This paper presents a comparative analysis of intelligent reflecting surface (IRS) technology versus conventional amplify-and-forward (AF) and decode-and-forward (DF) relay schemes in wireless communication. By focusing on transmit power, energy efficiency, and the minimum IRS elements required to outperform traditional relaying, we explore IRS’s potential as an energy efficient alternative. Our analysis shows that IRS configurations, especially with optimal phase shifts, achieve substantial power savings and superior energy efficiency over to AF and DF relays. Moreover, IRS requires fewer elements to meet or exceed relaying performance under higher data rate demands, making it an ideal choice for energy conscious, high performance network designs. These results highlight IRS technology as a promising solution for sustainable, next-generation communication networks.